CONSTRUCTION MATERIAL INTERFERENCE ON AIR TEMPERATURE AND HUMIDITY INSIDE THE PIGLET CREEP AREA - Sabino, Luana Araujo; de Abreu, Paulo Giovanni; Júnior, Vilmar Rodrigues de Sousa; Abreu, Valéria Maria Nascimento; Coldebella, Arlei (ENERGIA NA AGRICULTURA, 2015)
Piglet development in the farrowing house is a determining factor for the economic success of the farm, being essential to use means to ensure the survival and the satisfactory performance of the piglets in this phase. The objective was to evaluate the thermal comfort of two different creeps for piglets. For this, it was used a farrowing house with four individual pens, two made of wood, and two of polyethylene. Inside each creep and at the geometric center of each room, a data logger was installed to record temperature and humidity. Data were collected in four batches every 30 minutes for three weeks. These variables were analyzed using a repeated measures model. The polyethylene creep was the most suitable with 27.36% and 27.19% of the data within the comfort range, while the wooden creep achieved 13.61% and 23.85%, in the weeks 1 and 2, respectively. Only on the third week the wood creep presented better results, with 42.45%, whereas that of polyethylene attained 16.52% of the data within the comfort range. The creeps building materials had influence on the inner air temperature and humidity, and may affect the animals performance. Generally, the polyethylene creep provides better comfort conditions for piglets. KEYWORDS: Farrowing, welfare, swine. INTERFERÊNCIA DO MATERIAL DE CONSTRUÇÃO NA TEMPERATURA E UMIDADE DO AR NO INTERIOR DO ESCAMOTEADOR RESUMO: O desenvolvimento de leitões na maternidade é um fator determinante para o sucesso econômico de granjas, sendo essencial usar meios para alcançar desempenho satisfatório dos animais nestas fase. O objetivo deste trabalho foi avaliar o conforto de dois diferentes tipos de escamoteadores para leitões. Para isto, foi usado uma instalação de maternidade com baias individuais: duas feitas de madeira e duas de polietileno. Foi instalado um data logger dentro de cada escamoteador para registrar a temperatura e umidade do ar. Os dados foram coletdos em 4 lotes de animais por 30 minutos por três semanas. Estas variáveis foram analisadas usando um modelo de medidas repetidas. O escamoteador de polietileno foi o mais adequado com 27,36% e 27,19% dos dados dentro da zona de conforto dos animais, enquanto o escamoteador construído de madeira alcançou 13,61% e 23,85% nas semanas 1 e 2, respectivamente. Somente na terceira semana, o escamotedor de madeira apresentou melhores resultados, com 42,45% enquanto que os de polietileno atingiram 16,52% dos dados dentro da zona de conforto. Os materiais de construção dos escamoteadores tiveram influência na temperatura e umidade do ar e podem afetar o desempenho animal. Em geral, o escamoteador de polietileno forneceu uma melhor condição de conforto para os leitões. PALAVRAS-CHAVE: Maternidade, bem-estar, suíno.